2012
DOI: 10.1016/j.bpc.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inactivation of ocriplasmin in porcine vitreous

Abstract: Ocriplasmin, a 249-amino acid recombinant C-terminal fragment of human plasmin, has the potential to degrade, within the eye, the protein scaffold that links the vitreous to the retina. This may be beneficial to the treatment of a number of important ophthalmic indications, such as symptomatic vitreomacular adhesion. We demonstrate here that ocriplasmin used at therapeutically-relevant concentrations is inactivated in porcine vitreous through autolytic degradation. Autolytic cleavage occurs at a limited number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…Over time at þ378C and at pH 7.2, the intact ocriplasmin band decreased in intensity under reducing conditions, whereas the two main cleavage products of a lower molecular weight of approximately 16 and 9 kDa, respectively, were formed by cleavage of peptide bond 155 Leucine-156 Lysine. 12 Cleavage of ocriplasmin peptide bond 155 Leucine-156 Lysine fully inactivates the enzyme (data not shown). A very low intensity product could be seen at approximately 3 kDa, most likely corresponding to the 19 amino acids released from ocriplasmin's heavy chain under reducing conditions.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Over time at þ378C and at pH 7.2, the intact ocriplasmin band decreased in intensity under reducing conditions, whereas the two main cleavage products of a lower molecular weight of approximately 16 and 9 kDa, respectively, were formed by cleavage of peptide bond 155 Leucine-156 Lysine. 12 Cleavage of ocriplasmin peptide bond 155 Leucine-156 Lysine fully inactivates the enzyme (data not shown). A very low intensity product could be seen at approximately 3 kDa, most likely corresponding to the 19 amino acids released from ocriplasmin's heavy chain under reducing conditions.…”
Section: Resultsmentioning
confidence: 94%
“…The best fit for linearization of the concentration curve over time is obtained by using a concentration À1 versus time plot, indicating that inactivation of ocriplasmin is subject to a second-order kinetic process. 12 The resulting rate constant is 207 6 60 M À1 s À1 in PBS (n ¼ 3), whereas in vitreous it is 81 6 15 M À1 s À1 (n ¼ 3).…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that although this may in part reflect a difference in chemical structure of the vitreous adjacent to the vitreous base, it might reflect a lack of exposure to the enzyme that has to diffuse further to this particular location from its site of injection. This raises the question as to whether other factors, such as variable diffusion through the vitreous and variations in drug preparation and injection technique, might also influence the effect of the drug with its short half-life [19]. The distribution of retinal breaks would also concur with this, in that the breaks were not concentrated in the superotemporal quadrant as found in spontaneous PVD-related tears and RRD [20].…”
Section: Discussionmentioning
confidence: 99%
“…Microplasmin catalyses the cleavage of peptide bonds of lysine and arginine protein substrates leading to vitreous liquefaction and posterior vitreous detachment (de Smet et al 2009a,b;Gad El Kareem et al 2010a,b;Aerts et al 2012). Shortly after injecting microplasmin in the vitreous cavity, enhanced diffusion of microparticles and of fluorescein can be demonstrated (Sebag et al 2007;Gad El Kareem et al 2010a,b).…”
Section: Discussionmentioning
confidence: 99%